Quinta de paços. Uma intervenção em Contexto Rural - Vítor Manuel Soares Teixeira (2010)
Coming home... the neighbor's home, to revisit a known place - almost intimate - to have a new perspective on things, to notice things that went unnoticed before, and an urge to intervene aided by the opportunity to do so. This is how I would define my position in relation to the work presented here. Given the importance of this work as a culmination of a course of studies in order to establish myself as an architect, I present this as a confrontation of the academic knowledge obtained throughout my studies, applied to a new context - the current scenario - which is near to the professional activity, with new actors and renewed circumstances that this activity (in a way pre-professional) has started to sediment. In short, the work focuses on the reflection over a proposal for rehabilitation of a rural farm in Tarouquela - a village in the municipality of Cinfães (district of Viseu). It is a request / commission from a client who intends to take the project further, to the Licensing Stage in the near future. The work here presented acts as a Preliminary Stage due to a number of elements (designed and written) that will be part of the constitution of the Licensing Process. The work is structured in three main points: an Approach; one of Intervention and the third that I would call Reaction (in the manner of a conclusion). At first I present the backgrounds in different aspects - physical, historical, cultural transformation, ... - of space, of its organization towards an approach with the area of study, as well as the specific circumstances of work (client / program) in the way that they determin the development of work In the Second phase, the intervention proposal is presented, according to the themes / topics of reflection that guide the project - and its constituent parts - seeking to build a discourse open to references in the field of architecture, allowing for a good harvest of related elements. In the third part I intend to briefly outline a personal point of view about what will come out of this work: the reflection that I built; the issues raised; and all the elements that this study allowed to bring to light; in a more or less enlightened way, more or less accurate, but that in the end consists of what I presently enabled myself to develop and build. Learning is also a construction... a collective and continuous construction.